Pharmacokinetics of Tylvalosin in Broiler Turkeys (Meleagris Gallopavo) After Single Intravenous and Oral Administration - Elbadawy, Mohamed; Aboubakr, Mohamed; Abugomaa, Amira (Frontiers in Veterinary Science, 2019)
Pharmacokinetics of tylvalosin (TVN) were determined in eight broiler turkeys following a single intravenous (IV) and peroral (PO) administration of 25 mg/kg b.w using crossover design with a 3 weeks washout period. Blood samples were taken between 0.083 and 24 h following TVN administration, plasma was separated and assayed for TVN concentrations by HPLC. The non-compartmental analysis was used to analyze plasma concentration-time curves. After IV administration, the pharmacokinetic profile was best described by a two-compartment model. The mean distribution and elimination half-lives were 0.382 and 5.71 h, respectively. The distribution volume at steady state, total body clearance and mean residence time were 8.30 L/kg, 1.17 L/h and 7.16 h, respectively. After administering orally, the mean absorption half-life and absorption time of TVN was 0.955 and 2.31 h, respectively. The peak plasma concentration was 1.08 μg/mL and achieved at 2.0 h post-administration and the bioavailability was 53.3%. The plasma protein binding percent was 13%. For a successful clinical efficacy of TVN in broiler turkeys, a dosage regimen of 25 mg/kg b.w, given orally each day is recommended to keep efficient plasma levels above the MIC for most susceptible microorganisms.